Religious Moderation as A Solution of Interfaith Marriages in Multicultural Society - Ramadhan, Dian; Qolyubi, Imam (LPPM Universitas Lampung, 2021)
Multicultural implies the differences. If it is managed properly, the multicultural can generate the positive strength for national development. Conversely, if not managed properly, pluralism and multiculturalism can be destructive factors and lead to catastrophic disasters. Based on the plurality, in the field of marriage law, there is an element of pluralism or multicularism with the occurrence of interfaith marriages. This marriage occurred khilfaiyah (differences) of opinion among the scholars. There are some of them who allow interfaith marriages with the limitation that they only allow to marry women who are ahl al-Kitab, while other scholars strictly prohibit interfaith marriages. This research was a library research using descriptive analysis method. In this case the author sought to describe and analyze religious moderation as a solution to interfaith marriage in a multicultural society. The result of this research is that marriage between Muslim men and women of scripture is allowed if in their actions there is a benefit and does not cause damage or harm in accordance with the principle of